Factors Affecting Number of Women Ward Councillors in South Africa - Majola, Brian Kwazi (Journal of Reviews on Global Economics, 2020)
The number of women elected into political positions has been a challenge for both developed and developing states. Countries that have introduced national prescripts and ratified the United Nations conventions continue to struggle with women's representation and participation in politics, especially at the local government level. South Africa is not an exception to this. Despite legislation that appears to enable gender equality in local structures, the number of women ward councillors has been fluctuating since the reformation of local government after 1994. The objective of this paper is to investigate factors affecting the number of women elected as ward councillors in South Africa. The paper adopts an exploratory research design and is qualitative in nature. It focuses on six local municipalities of the KwaZulu-Natal and Eastern Cape Provinces. Males and female ward and proportional representative councillors were interviewed using face-to-face and telephone techniques. The findings of the study were analysed using content analysis and themes were generated from the interview data. The study revealed that there are more women proportional representative councillors than ward councillors, which confirms the challenge with regard to women’s representation in local politics. The number of women councillors is low and some major factors identified in the study were lack of confidence, education and community involvement; cultural influence; and competitiveness amongst women.